The Correlation Between Classroom Management and Writing Learning Outcomes in Indonesian Language Subject for 5th Grade Elementary Students - Muhammad Saiful; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This study was motivated by the low writing achievement of Grade V students at SD Negeri 010 Hutapuli, Mandailing Natal Regency, which is suspected to be influenced by the suboptimal classroom management implemented by teachers. An unconducive learning atmosphere, ineffective student interaction, and inadequate classroom arrangement were found to negatively affect student motivation and participation in writing activities. Therefore, this research aims to examine the correlation between classroom management and students’ writing learning outcomes in Indonesian language subject. This study employed a quantitative method with a correlational approach. The population consisted of all Grade V students of SD Negeri 010 Hutapuli, totaling 40 students. The instrument used to measure classroom management was a questionnaire, while the students’ writing achievement was assessed through documentation of writing task scores. Data were analyzed using Pearson’s Product Moment correlation technique. The results showed that the correlation coefficient (r) was 0.724, which falls into the